2015
DOI: 10.1063/1.4918746
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic emission during the ferroelectric transition Pm3¯m to P4mm in BaTiO3 and the ferroelastic transition R3¯m-C2/c in Pb3(PO4)2

Abstract: Acoustic emission (AE) spectroscopy without frequency filtering (∼broadband AE) and moderate time integration is shown to be sensitive enough to allow the investigation of subtle nano-structural changes in ferroelectric BaTiO3 and ferroelastic Pb3(PO4)2. AE signals during weak phase transitions are compatible with avalanche statistics as observed previously in large-strain systems. While the data are too sparse to determine avalanche exponents, they are well suited to determine other thermodynamic parameters s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Some experimental methods, such as AFM, diffuse X‐ray, or neutron scattering, and some transport measurements, measure N. Other methods explore the dynamics of moving domain walls (DMA, RUS, and RPS ) and find strong singularities near the ferroelastic transition point even when the transition is continuous. The transition always appears stepwise in these experiments, such as a burst of acoustic emission signals when the domain walls form . This observation is similar to the results of random first order transitions (RFOT) discussed by Kirkpatrick and collaborators for structural glasses and in the field of turbulence .…”
Section: Four Domain Glass Temperaturessupporting
confidence: 87%
See 1 more Smart Citation
“…Some experimental methods, such as AFM, diffuse X‐ray, or neutron scattering, and some transport measurements, measure N. Other methods explore the dynamics of moving domain walls (DMA, RUS, and RPS ) and find strong singularities near the ferroelastic transition point even when the transition is continuous. The transition always appears stepwise in these experiments, such as a burst of acoustic emission signals when the domain walls form . This observation is similar to the results of random first order transitions (RFOT) discussed by Kirkpatrick and collaborators for structural glasses and in the field of turbulence .…”
Section: Four Domain Glass Temperaturessupporting
confidence: 87%
“…The concept of “Domain Glass” was introduced in 2014 while “domain” related glass states (such as encountered in polar nano‐regions) were long understood to exist in relaxor materials where non‐ergodicity is one of the defining properties of the relaxor state . However, little is known about how the breaking of ergodicity occurs in the limiting case of weakly disordered systems.…”
Section: Introductionmentioning
confidence: 99%
“…Baró et al (2013) reported a very complete parallel between the acoustic emissions produced by a porous material under uniaxial compression and earthquakes. The same experimental techniques are widely used for the investigation of device materials such as ferroelectric, ferromagnets, and ferroelastics (Bolgár et al 2016;Dul'kin et al 2015;Guyot et al 1988;Hoffmann et al 2001;Salje et al , 2015Skal's'kyi et al 2009;Vives et al 1994) with a significant increase of published data over recent years on the acoustic emission during force-induced changes of microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…Avalanches are largely scale invariant and are described by statistical quantities. 15 Jerks were observed in heat flux measurements (thermal jerks), 17 AE (acoustic jerks) and slip avalanches in metallic glasses, [18][19][20][21][22][23][24] spikes in the polarization (electric jerks), and Barkhausen noise 2,14 (magnetic jerks). Each jerk signal is characterized by fairly random, often jagged profiles so that the question arises: is the time evolution predictable if one considers the averaged profiles?…”
mentioning
confidence: 99%